2004
DOI: 10.1590/s1415-54192004000400005
|View full text |Cite
|
Sign up to set email alerts
|

Composição química e resistência mecânica da base de braquetes "Straight-Wire"

Abstract: Esse trabalho objetivou comparar as durezas superficiais e as características metalográficas das bases de braquetes "straight-wire" de quatro marcas comerciais: Morelli, Abzil Lancer, Unitek e A-Company. As durezas superficiais foram avaliadas por meio de um teste de dureza realizado com o auxílio de um microdurômetro. Os resultados indicaram diferenças entre as marcas comerciais testadas onde os braquetes da A-Company apresentaram os valores mais altos de dureza (314 HV), seguidos da Unitek (325 HV), Abzil (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
7

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
0
1
0
7
Order By: Relevance
“…For this reason, nickel-free alloys or alloys of stainless steel with reduced amount of nickel have been tested. 17 Studies 1,4,8,11,12,18,27 confirmed the possibility of in vivo and in vitro corrosion of steel brackets and associated a lower or greater potential of corrosion not only to the metal used, but to the manufacturing process and to the final structure of these appliances. The pure titanium was recently introduced as alternative material for metallic brackets for its low allergenicity, greater corrosion resistance 10 (inferior to gold and platinum only), biocompatibility and good mechanical resistance.…”
Section: Introductionmentioning
confidence: 84%
“…For this reason, nickel-free alloys or alloys of stainless steel with reduced amount of nickel have been tested. 17 Studies 1,4,8,11,12,18,27 confirmed the possibility of in vivo and in vitro corrosion of steel brackets and associated a lower or greater potential of corrosion not only to the metal used, but to the manufacturing process and to the final structure of these appliances. The pure titanium was recently introduced as alternative material for metallic brackets for its low allergenicity, greater corrosion resistance 10 (inferior to gold and platinum only), biocompatibility and good mechanical resistance.…”
Section: Introductionmentioning
confidence: 84%
“…A comparação entre as diversas marcas comerciais de acessórios ortodônticos confi rmou os achados de Gontijo 12 quanto à falta de padronização das curvaturas das bases dos braquetes. Além disso, demonstrou que nenhum braquete comercial apresentava uma geometria da base similar àquela da superfície dentária para as amostras avaliadas (Tab.…”
Section: Discussionunclassified
“…Para a construção das bases dos braquetes no ambiente tridimensional utilizou-se as medidas encontradas em estudo prévio 12 Os modelos em elementos finitos criados representaram a interface superfície do esmalte, camada adesiva e base de braquete correspondentes às marcas testadas. Empregou-se o programa para a análise numérica Algor com os módulos Superdraw III e SuperView, que possibilitou efetuar as etapas de pré-processamento, cálculos matemáticos e pós-processamento dos problemas.…”
Section: Materiais E Métodosunclassified
See 2 more Smart Citations